2008
DOI: 10.1021/jp805280r
|View full text |Cite
|
Sign up to set email alerts
|

Positron Annihilation Lifetime Spectroscopy (PALS) as a Characterization Technique for Nanostructured Self-Assembled Amphiphile Systems

Abstract: Positron annihilation lifetime spectroscopy (PALS) has potential as a novel rapid characterization method for self-assembly amphiphile systems; however, a lack of systematic correlation of PALS parameters with structural attributes has limited its more widespread application. In this study, using the well-characterized phytantriol/water and the phytantriol/vitamin E acetate/water self-assembly amphiphile systems, the impact of systematic structural changes controlled by changes in composition and temperature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 58 publications
0
68
0
Order By: Relevance
“…Further, more understanding of thermalization and trapping mechanisms and their effectiveness in not only nanocrystalline but also amorphous and molecular matter is needed on a general level. In soft and molecular matter, the most important information in the annihilation signal is often contained in the pick-off annihilation of ortho-Ps (the positron within triplet positronium annihilating with outside electrons); see, e.g., Tao (1972), Eldrup, Lightbody, and Sherwood (1981), Jean (1990), Hirata, Kobayashi, and Ujihira (1996), Dong et al (2009), Sane et al (2009), and Quinn et al (2012. This correlated state involving also nonlocal correlations (van der Waals interaction) with the surroundings is extremely challenging to model for any realistic system [see Platzman (2009) andPuska (2012)].…”
Section: B Positron States At Interfaces and Surfacesmentioning
confidence: 99%
“…Further, more understanding of thermalization and trapping mechanisms and their effectiveness in not only nanocrystalline but also amorphous and molecular matter is needed on a general level. In soft and molecular matter, the most important information in the annihilation signal is often contained in the pick-off annihilation of ortho-Ps (the positron within triplet positronium annihilating with outside electrons); see, e.g., Tao (1972), Eldrup, Lightbody, and Sherwood (1981), Jean (1990), Hirata, Kobayashi, and Ujihira (1996), Dong et al (2009), Sane et al (2009), and Quinn et al (2012. This correlated state involving also nonlocal correlations (van der Waals interaction) with the surroundings is extremely challenging to model for any realistic system [see Platzman (2009) andPuska (2012)].…”
Section: B Positron States At Interfaces and Surfacesmentioning
confidence: 99%
“…Positron annihilation lifetime spectroscopy (PALS) has emerged as an advanced and relatively new approach to investigate the size and size distribution of free volume elements in polymers [19][20]. This method is based on the measurement of positron lifetime and lifetime intensity in a material.…”
Section: Free Volume Analysismentioning
confidence: 99%
“…The annihilation of positrons in a polymer occurs via several pathways. One of the pathways, based on o-Ps in the triplet spin state, is typically sensitive to free volume elements in a polymer, including their size (characterised by o-Ps lifetime τ 3 ) and concentration (characterised by intensity I 3 ), respectively [20].…”
Section: Free Volume Analysismentioning
confidence: 99%
“…PALS is a well -established technique used for investigating chain packing and nanostructure in polymer (Ata et al, 2009 ;Misheva et al, 2000 ) high -viscosity liquid (Jain, 1995 ) and recently lyotropic liquid crystals (Dong et al, 2009 ). It is used to provide an atomic -scale probe of the dimensions of free volume within materials, based on the lifetime of orthopositronimum (oPs) localized in inter -and intramolecular spaces.…”
Section: Positron Annihilation Lifetime Spectroscopymentioning
confidence: 99%
“…However, there is a lack of systematic correlation of PALS parameters with molecular structure. Dong et al (2009) have compared the relationship between the oPs lifetime and rheology of mesophases summarized in Figure 4.8 . They found that the oPs lifetime is correlated with rheological properties, lipid chain packing (d spacing), and mobility in various mesophases.…”
Section: Positron Annihilation Lifetime Spectroscopymentioning
confidence: 99%